Penyuluhan Stunting Guna Meningkatkan Pengetahuan Dan Pencegahan Di Desa Padang Mutung Kecamatan Kampar - Al Fiqri, Yanuar; Pradipta Rizki, Rini; Lesmana Pratama, Jody; Julian Sugfa, Yogi; Zayyan Hibrizi, Adib; Nuratika, Sagita; Aprilia, Miranda; Salsabila Azis, Dhanti; Emirabana, Shery; Elok Rahmawati, Fida; Dayani, Ulfa (Politeknik Negeri Jember, 2024)
Kuliah Kerja Nyata (Kukerta) is a form of community service activities by students with a cross-scientific and sectoral approach at a certain time and area. Implementation. The implementation of Kukerta Bangun Kampung Riau University was carried out for 40 days in a village-level area. The implementation of this Kukerta started on July 10, 2023 until August 18, 2023 in Padang Mutung Village, Kampar District, Kampar Regency. Kukerta UNRI Padang Mutung has a flagship program, namely Stunting Counseling with the target of pregnant women and toddlers. This program aims to provide education to parents about the importance of stunting knowledge for child development and is expected to increase public awareness and understanding of stunting prevention efforts. The method of implementing this activity begins with collecting data on stunting in Padang Mutung Village and continues with the delivery of material accompanied by weighing activities, measuring height and providing nutritious food. This activity was carried out in the Padang Mutung Village office hall and went well